The DNA methylation landscape of human cancer organoids available at the American type culture collection. Issue 11 (1st November 2020) - Joshi, Ricky; Castro De Moura, Manuel; Piñeyro, David; Alvarez-Errico, Damiana; Arribas, Carles; Esteller, Manel
ABSTRACT: One caveat in cancer research is the dependence of certain experimental systems that might not really reflect the properties of the primary tumours. The recent irruption of 3D cultured cells termed organoids could render a better representation of the original tumour sample. However, every laboratory has its own protocol and tissue-provider to establish these cancer models, preventing further dissemination and validation of the obtained data. To address this problem, the Human Cancer Models Initiative (HCMI) has selected the American Type Culture Collection (ATCC) to make available organoid models to the scientific community. In this regard, no epigenetic information is available for these samples and, overall, the DNA methylation profiles of human cancer organoids are largely unknown. Herein, we provide the DNA methylation landscape of 25 human cancer organoids available at the ATCC using a microarray that interrogates more than 850, 000 CpG sites. We observed that the studied organoids retain the epigenetic setting of their original primary cancer type; that exhibit a DNA methylation landscape characteristic of transformed tissues excluding an overgrowth of normal-matched cells; and that are closer to the DNA methylation profiles of the corresponding primary tumours than to established 2D cell lines. Most importantly, the obtained DNA methylation results are freely available to everyone for further data mining. Thus, our findings support from the epigenetic standpoint that the ATCC human cancer organoids recapitulate many of the features of the disorder in the patient and are excellent tools to be shared among investigators for further tumour biology research.